Clinical Therapy of Metastatic Spinal Tumors - Li, Jie; Wei, Wenjie; Xu, Feng; Wang, Yuanyi; Liu, Yadong; Fu, Changfeng (Frontiers in Surgery, 2021)
Metastatic spinal tumors (MST) are associated with high rates of morbidity and mortality. MST can destroy the vertebral body or compress the nerve roots, resulting in an increased risk of pathological fractures and intractable pain. Here, we reviewed the currently available therapeutic options for MST in terms of the following four aspects: surgical management, minimally invasive therapy (MIT), radiation therapy, and systemic therapy. In particular, these aspects were classified and introduced to show their developmental process, clinical effects, advantages, and current limitations. Furthermore, with the improvement of treatment concepts and techniques, we discovered the prevalent trend towards the use of radiation therapy and MIT in clinic therapies. Finally, the future directions of these treatment options were discussed. It is hoped that along with future advances and study will lead to the improvement of living standard and present status of treatment in patients with MST.